Assessment of Aspergillus‐specific PCR as a screening method for invasive aspergillosis in paediatric cancer patients and allogeneic haematopoietic stem cell recipients with suspected infections. Issue 9 (21st March 2014) - Reinwald, M.; Konietzka, C. A. M.; Kolve, H.; Uhlenbrock, S.; Ahlke, E.; Hummel, M.; Spiess, B.; Hofmann, W.‐K.; Buchheidt, D.; Groll, A. H.
Summary Invasive aspergillosis (IA) remains difficult to diagnose in immunocompromised patients, because diagnostic EORTC/MSG criteria are often not met. As biomarkers might elucidate the pathogen, we analysed the performance of an Aspergillus PCR assay in blood for diagnosis of IA in immunocompromised paediatric patients with suspected infections. Ninety‐five haemato‐oncological paediatric patients were included over a period of 3 years, the underlying diseases consisting of acute leukaemia, solid tumours, non‐malignant immunocompromising disorders and haematopoietic stem cell transplantation recipients. We retrospectively analysed 253 consecutive episodes of suspected infections. Thirty‐eight patients had possible IA, none of the patients fulfilled EORTC/MSG criteria of probable/proven IA. PCR positivity was observed in 97/967 analyses. Sensitivity, specificity, positive and negative predictive value of the PCR per episode were 34%, 78%, 31% and 81% using possible IA as endpoint. Taken together, an undirected blood screening by Aspergillus‐specific PCR is of little diagnostic value in a heterogenous paediatric patient cohort. Harnessing PCR for diagnosis of IA should thus be focused on blood analyses of more homogenous high‐risk patients and/or analyses of bronchoalveolar lavage, tissue or cerebrospinal fluid specimens.